Development of a Gustatory Function Test for Clinical Application in Korean Subjects - Hwang, Chi Sang; Kim, Jin Won; Al Sharhan, Salma Saud; Kim, Jin Woong; Cho, Hyung-Ju; Yoon, Joo-Heon; Kim, Chang-Hoon (Yonsei medical journal, 2018)
To obtain validated clinical values suitable for developing a gustatory function test, including umami taste, in a Korean population. The investigation involved 297 participants with self-reported normal sense of taste and smell. Liquid solutions were used for the assessment of gustatory function. The test consisted of 30 taste solutions [six concentrations of five tastants (sweet, bitter, salty, sour, and umami)]. For evaluation of overall gustatory function, the number of detected or correctly recognized taste thresholds was combined to form a "taste score." Mean values of each detection and recognition threshold for the five tastes in men were consistently lower than those of women. The 10th percentile of taste score for recognition was used as the cut-off value for distinguishing normogeusia from hypogeusia. In subgroup analysis, total taste score from recognition thresholds revealed a significant negative correlation with age, indicating lower scores for increasing age. Taste score for non-smokers was significantly higher than that of smokers, in terms of detection and recognition of taste sensitivities. This gustatory function test was easy to perform, affordable, and time-saving, with the capacity to self-produce and obtain reliable data. Gustatory function was more sensitive in young people, women, and non-smokers.